Geo explorer a geographical information system for the Philippines' geological features - Gumihid, Annelle D.
The primary goal of GEO EXPLORER is to take raw data and transform it via overlays and other operations into new information which could be very helpful in decision making. To be able to achieve this, substantial information relevant to the topic, mainly of the capabilities of certain softwares that would aid them in the reading of the maps' file format such as Dr. DWG, was acquired and mastered. This, in a nutshell has been the vision of the GEO EXPLORER Research Group as we went through the completion of the project. More closely, since GEO EXPLORER dealt with a lot of maps, the research project initially was oriented with Cartography and the concepts behind it with emphasis on Computer Cartography. Its influenced on Cartography has opened up cartographic methods and techniques to more general purpose uses of geographic information. Nowhere has this been more evident than in the field of Geographic Information System (GIS). GEO EXPLORER basically being GIS, makes familiarization with the different kinds of existing GIS's vital to this project. Nowadays, specifically in the National Institute of Geological Sciences (NIGS), existing updated geological information in the form of maps are processed through AutoCAD with digitized maps being inputs. These geological maps are in the form of DWG files created through AutoCAD. These files being not accessible to other applications such as for the purpose of GEO EXPLORER must be converted to DXF files. Through the capabilities of Dr. DWG we were able to work with the maps. Since Visual Basic is the primary language that was used, its matter was another important objective. Given different constraints, the group was able to acquire resources, some published, others downloaded, and do substantial research on the topics mentioned. We became oriented with Computer Cartography and succeeded in familiarizing ourselves with some existing GIS's mainly through net surfing. As to Image Processing specifically with DXF files, we were able to make use of the capabilities offered by Dr. DWG in creating GEO EXPLORER.